2012
DOI: 10.1175/jcli-d-11-00135.1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Tibetan Plateau Snow Cover on the ENSO Teleconnections: From the East Asian Summer Monsoon Perspective

Abstract: The East Asian summer monsoon (EASM) may exhibit rather large variability between years characterized by the same ENSO phase. Such inconsistency reduces the EASM predictability based on ENSO. Results in this study show that the Tibetan Plateau snow cover (TPSC) exerts a modulating effect on ENSO teleconnections and ENSO significantly correlates with the EASM only during the reduced TPSC summers. Three-dimensional circulation structures are examined to manifest that the typical ENSO signals in reduced TPSC summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 37 publications
3
84
0
Order By: Relevance
“…The origin of the EOF1 and EOF3 patterns over the pre-industrial period is not clearly established yet, even though both of them may be related to the movement and intensity of the western Pacific subtropical high during the instrumental period (Wu and Wang, 2002). Moreover, some studies show that other factors such as the North Atlantic Oscillation (NAO) Zheng et al, 2016) and the North Atlantic three-pole SST pattern (Ruan and Li, 2016), the interdecadal Pacific oscillation (IPO) (Song and Zhou, 2015), the snow cover change of the Tibetan Plateau (Ding et al, 2009;Wu et al, 2012), and some regional processes in China may contribute to the precipitation field modes during the instrumental period. Thus, additional studies are required to determine which of these processes might be related to EOF1 and EOF3 over the pre-industrial period.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the EOF1 and EOF3 patterns over the pre-industrial period is not clearly established yet, even though both of them may be related to the movement and intensity of the western Pacific subtropical high during the instrumental period (Wu and Wang, 2002). Moreover, some studies show that other factors such as the North Atlantic Oscillation (NAO) Zheng et al, 2016) and the North Atlantic three-pole SST pattern (Ruan and Li, 2016), the interdecadal Pacific oscillation (IPO) (Song and Zhou, 2015), the snow cover change of the Tibetan Plateau (Ding et al, 2009;Wu et al, 2012), and some regional processes in China may contribute to the precipitation field modes during the instrumental period. Thus, additional studies are required to determine which of these processes might be related to EOF1 and EOF3 over the pre-industrial period.…”
Section: Resultsmentioning
confidence: 99%
“…Yeh et al (2009) found that the frequency of the central Pacific El Niño events increased noticeably after 1990. Wu et al (2011b) suggested that the Tibetan Plateau snow cover may modulate the ENSO-related teleconnections. Therefore, the interdecadal changes of the ENSO and associated atmospheric teleconnections are complicated and have multiple aspects and different periods.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Anomalous snow events are clearly related to El Niño and La Niña. Most of the current research is about how snow cover in Tibet affects the summer-monsoon, particularly during ENSO years [13,21,50]. How ENSO affects snow cover in Tibet is also discussed [51].…”
Section: Annual Snow Cover Distributionmentioning
confidence: 99%